Досвід використання технологій Е-learning у вищому навчальному закладі - Яковенко, Ю. Л.; Хорошайло, О. С.; Khoroshailo, O. S.; Yakovenko, Yu. L. (Інтернаука, 2017)
Стаття присвячена проблемі використання сучасних технологій в умовах ВНЗ. Розкрито переваги та недоліки такого методу. Відображено досвід використання Е-learning при викладанні дисциплін гуманітарного циклу та іноземної мови студентам ВНЗ. Виявлено доцільність впровадження таких технологій у навчальний процес.

The article is devoted to the use of modern technologies in the context of the university. The advantages and disadvantages of such methods are revealed. It describes the experience of using E-learning in teaching students humanitarian subjects and foreign languages. The expediency of introducing such technologies in the educational process is proved.
Experience in the use of e-learning technologies in the higher educational establishment
Keywords: Е-learning; m-learning; інформація; інформаційні та комунікаційні технології; навчання; освіта; information; information and communication technologies; training; education